Humanism and the early modern essay - Jones, Darrell (Trinity College (Dublin, Ireland). School of English, 2014)
This is a thesis about the emergence, establishment, and development of the early modern essay and the relationships of those processes to various forms of humanism. The essay is considered both as a conceptual entity, that is, a literary form or genre, and as a bibliographical sign, that is, a widely used title for printed books and pamphlets. Humanism is defined partly as the cultural promotion of classical and vernacular philology and civic engagement, and partly as the conviction that human agency and its attendant conditions were legitimate and essential objects of intellectual inquiry.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin